The use of digital marketing for optimizing the logistics supply chain and cost control - Ippolitova, Inna; Beketov, Yurii; Tatarinov, Vadym; Dobrianska, Viktoriia; Karpenko, Yevheniia (ТОВ "Фінтехальянс", 2024)
The aim of the research is to analyse the relationship between digital marketing and delivery failures and identify opportunities for optimization. The research employed the methods of statistical analysis, correlation analysis, comparative analysis, and analysis of metrics. The conducted research determined that one of the main challenges of the supply chain is failures caused by various reasons (lack of skills, diseases, transport failures, adverse weather conditions, cyber attacks, etc.). Disruptions often lead to delivery failures. The reasons for this often do not depend on the companies and bring significant negative consequences, in particular, in the form of losses, loss of reputation, and decreased customer loyalty. The study revealed that digital marketing indicators are positively correlated with non-delivery indicators. In particular, Social media interactions and Failures to deliver (0.75), Social media likes and Failures to deliver (0.74), Social media interactions and Biweekly Failures to deliver volume (0.78), Social media likes and Biweekly Failures to deliver volume (0.78). It was assumed that this state of affairs may be determined by increased demand due to digital marketing, for which companies may not always be ready. Insufficient preparedness can lead to disruptions because of supply chain congestion. The results can be useful for e-commerce companies to evaluate and minimize the number of failed deliveries.

Метою роботи є аналіз зв’язку між цифровим маркетингом і невиконанням доставок разом із виявленням можливостей для оптимізації. У дослідженні було застосовано методи статистичного аналізу, кореляційного аналізу, порівняльного аналізу й аналізу метрик. У результаті проведеного дослідження було визначено, що одним із основних викликів ланцюга поставок є збої, зумовлені різними причинами (брак навичок, захворювання, збої у транспорті, несприятливі погодні умови, кібератаки тощо). Збої часто призводять до невиконання доставки. Причини цього найчастіше не залежать від компаній і приносять суттєві негативні наслідки, зокрема, у вигляді збитків, утрати репутації, зниження лояльності клієнтів. У роботі було виявлено, що показники цифрового маркетингу позитивно корелюють із показниками стосовно невиконання доставок. Зокрема, Social media interactions та Failures to deliver (0,75), Social media likes та Failures to deliver (0,74), Social media interactions та Biweekly Failures to deliver volume (0,78), Social media likes та Biweekly Failures to deliver volume (0,78). Зроблено припущення, що такий стан справ може бути пов'язаний із зростанням попиту завдяки цифровому маркетингу, до чого компанії не завжди підготовлені. Недостатня готовність може призводити до збоїв через перевантаженість ланцюга поставок. Результати даного дослідження можуть бути корисними для компаній, що працюють у сфері електронної комерції, у цілях оцінки та мінімізації кількості невиконаних доставок.
Використання цифрового маркетингу для оптимізації логістичного ланцюга поставок та контролю витрат
Keywords: digital marketing; logistics supply chain; user loyalty; number of interaction; social networks; delivery failure; preferences; цифровий маркетинг; логістичний ланцюг поставок; лояльність користувачів; кількість взаємодій; соціальні мережі; невиконання доставок; уподобання